(untitled) (Baghdad Science Journal, 2005)
This experiment was conducted in the season 2001-2000 in station Ishaqi the company’s general industrial crops to plant livestock Vigna radala deleted (Khadrawi) carried out the experiment design panels splinter and order in RCBD with three balls two factors are levels nitrogen fertilizer (120 and, 100.0 kg urea / ha)nitrogen ratio of 46%, which put in the main panels mAIN PLOT and Alkiavat three levels that were placed in secondary panels .....